Impact of low blood culture usage on rates of antimicrobial resistance. Issue 3 (March 2021) - Lim, Cherry; Hantrakun, Viriya; Teerawattanasook, Nittaya; Srisamang, Pramot; Teparrukkul, Prapit; Sumpradit, Nithima; Turner, Paul; Day, Nicholas PJ; Cooper, Ben S; Peacock, Sharon J; Limmathurotsakul, Direk
Summary: Objectives: The magnitude of impact caused by low blood culture utilization on estimates of the proportions and incidence rates of antimicrobial-resistant (AMR) bacterial infections is largely unknown. Methods: We used routine electronic databases of microbiology, hospital admission and drug prescription at Sunpasitthiprasong Hospital, Ubon Ratchathani, Thailand, from 2011 to 2015, and bootstrap simulations. Results: The proportions of Escherichia coli and Klebsiella pneumoniae bacteraemias caused by 3rd generation cephalosporin resistant isolates (3GCREC and 3GCRKP) were estimated to increase by 13 and 24 percentage points (from 44% to 57% and from 51% to 75%), respectively, if blood culture utilization rate was reduced from 82 to 26 blood culture specimens per 1, 000 patient-days. Among patients with hospital-origin bloodstream infections, the proportion of 3GCREC and 3GCRKP whose first positive blood culture was taken within ±1 calendar day of the start of a parenteral antibiotic at the study hospital was substantially lower than those whose first positive blood culture was taken later into parenteral antibiotic treatment (30% versus 79%, p <0.001; and 37% versus 86%, p <0.001). Similar effects were observed for methicillin-resistant Staphylococcus aureus, carbapenem-resistant Acinetobacter spp. and carbapenem-resistant Pseudomonas aeruginosa . Conclusion: Impacts of low blood culture utilization rate on the estimated proportions and incidence rates of AMR infections could be high. We recommend that AMR surveillance reports should additionally include blood culture utilization rate and stratification by exposure to a parenteral antibiotic at the hospital.